Matthew - Allen, O. Wesley, 1965- (Minneapolis, MN : Fortress Press, 2013)
Traditional books on preaching a book of the Bible often look at broad themes of the text with little explicit advice about preaching individual passages. Lectionary resources often offer exegetical and homiletical insights about a pericope with little attention given to broader theme and structures of the book from which the lection is taken. In this book Wes Allen draws together the strengths of these two approaches into a new genre of homiletical and teaching resource with a focus on the Gospel according to Matthew. Matthew will not only be an essential classroom resourc.
Beginnings: From Bethlehem to Nazareth (1:1-4:11) -- Capernaum-Based Ministry (4:12-18:35) -- Traveling to Jerusalem (19:1-20:34) -- Passion, Death, and Resurrection in and around Jerusalem (21:1-28:15) -- Beginning Again in Galilee (28:16-20)
Includes bibliographical references.
Keywords: Bible. -- Criticism, interpretation, etc; Bible. -- Homiletical use